A COMPARATIVE STUDY OF EXTRACTION OPTIMIZATION, ANTIOXIDANT POTENTIAL, AND FATTY ACID COMPOSITION OF CUCUMI SATIVUS AND CUCUMIS MELO - Fakhar Abbas; Ayoub Rashid; Syed Ali Raza; Muhammad Imran Ul Haq; Sadia Haider; Khalid Hamid (International Journal of Pharmacy & Integrated Health Sciences, 2024)
Background: Cucumis plants are being frequently used to treat metabolic disorders such as obesity and diabetes, in traditional medicinal system. Objectives: The current study sought to assess the impact of several solvents with varying polarity for the extraction of polyphenolic, and flavonoid components. Further, this study also aims to determine antioxidant activity of fruits and peels of Cucumis melo and Cucumis sativus. Methodology: Methanol, ethyl acetate, chloroform, and n-hexane were chosen for optimal extraction. Extract yields were assessed to determine the optimal solvent solution for extraction. The TPC and TFC contents were determined by Folin–Ciocalteu reagent and AlCl3 method.  The antioxidant potential was determined spectrophotometrically using DPPH scavenging and iron chelation assays. The fatty acid contents of methanol extract were determined by gas chromatography (GC-FID). The instrument utilized for this purpose was a Shimadzu GC-14A with a flame ionizer (FID) and a packed glass column, DEXIL-300. The column oven's temperature was kept at 180ºC for 5 minutes and programmed to 250 ºC at the rate of 5ºC/mint. The injection and detector temperature was 250ºC and 230ºC respectively. Results: The results showed that the methanol extract of C. sativus peels exhibited the highest extraction yield, TPC, and TFC 12.72 ± 0.34 mg/mL, 130.13 ± 1.23 mg/mL, and 86.56 ± 0.67 mg/mL, respectively for C. Sativus peels and for C. melo the results were as 8.32. ± 0.34 mg/mL, 68.23.13 ± 1.23 mg/mL and 48.23 ± 0.67 mg/mL, respectively. The C. Sativus peel extract also showed the highest DPPH inhibition and iron chelation activities with IC50 values of 33.34 ± 0.12 µg/mL and 30.34 ± 0.23 µg/mL. The methanol extracts also showed dose-dependent antioxidant activities. The seven fatty acids contents were found from C12 to C20 in peel extract with arachidic acid and linoleic acid in relatively greater amounts. Conclusion: The current study has shown that the methanol extract of C. sativus peel has rich total phenolic, flavonoid content, and has reasonable antioxidant activity in all of the tested methods.